The Effects of Frequency and Pivot Flexibility on the Dynamic Properties of Tilting-Pad Journal Bearings - Laurence F. Wagner; Paul E. Allaire (Research Developments in Science and Technology Vol. 5, 2022)
Tribologists have generally accepted that the dynamic modeling of tilting-pad journal bearings (TPJB) must consider the frequency dependency of the dynamic properties. Industrial compressors, turbines, and other rotating machines are subjected to instability drivers, such as blades, impellers, and seals, leading to dominant vibratory frequencies that are generally quite different from rotational frequency. Though the literature has provided related methods and numerical results, full understanding of the physics of TPJB frequency dependency is not generally available to the design community, and theorists and experimentalists are often not in agreement. This investigation hinges on a single-pad, two degree-of-freedom model that creates a basis for understanding the various geometries and operating conditions related to frequency dependency for a full bearing. The analytical results indicate that both stiffness and damping coefficients show frequency dependency, and that the dependency is primarily associated with the pad rotational damping and the flexibility of the pivot contact region that provides support for the pad. This study attempts to provide an understanding of the role of pivot flexibility in combination with the fluid film to help support analysts seeking agreement between theory and experiment. This article is a revised and expanded version of the paper presented at the ASME 2019 Turbo Expo in Phoenix, Arizona from 17 to 21 June. The paper number was GT2019-90195 and it was titled “On the Frequency Dependency of Tilting-Pad Journal Bearings.”